The Frequency of Varying Degrees of Gingival Display and Biometric Measurements of Anterior Teeth - Hina Zafar Raja, Besam Babar, Afsheen Zakir, M. Abu Bakar Sadaqat, Hunza Zaheer Chattha, Abdul Moiz Bin Hamid, Sajid Naeem (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find out the frequency of gingival display in dentate individuals while smiling and evaluate the biometric measurements of anterior teeth at varying degrees of display. Study design: Cross sectional observational study. Place and duration: Prosthodontic Department of Lahore Medical and Dental College Lahore, from 5-6-2022 to 05-09-2022 Methodology: Selected subjects comfortably seated in dental chair. Digital vernier caliper was used for recording of measurements. Each individual was asked for maximum smile and gingival display noted as visible or not. Biometric measurements e.g.; over jet, over bite were recorded for gingival displayedand non -displayed group. Results: A total of 260 subjects including 49.2% males and 50.8% females were selected. The mean age of the subjects was 22.81±SD 2.087 years. 65.4% of individuals had gingival display whereas 34.6 % did not show gingiva while posed smiling. Gender distribution showed more display of gingiva in females 72.7% as compared to males 57.8%. Statistically significant results were obtained when compared i.e.; p<0.05. The over bite values showed significant difference with respect to gender however the over jet had insignificant difference with respect to gender. The comparison of means of biometric measurements with gingival display and non-display group showed significance. The values of over jet obtained in gingival display and non-display group were 3.30±0.728 and 2.34±0.829 whereas the mean values of over bite obtained in both groups were 2.97± 0.625 and 2.78±0.625. Conclusion: Gingival display is frequently observed in our region. Gender based difference exists with respect to gingival display level where females displaying more gingival tissue and significant variation is seen in the biometric measurements of displayed and non -displayed group.These findings would help in placing margins of fixed and removable prosthesis in best esthetic zone. Key words: Anterior teeth, Dentate, Esthetics, Gingiva, Gingival display, Over jet, Over bite, Smile,